LUCAS: development and validation of a simple mortality risk calculator that predicts 60-day survival of adult SARS-CoV-2 positive patients at hospital admission using rapid routine tests - Ray, S; Swift, A; Fanstone, JW; Banerjee, A; Mamalakis, M; Vorselaars, B; Mackenzie, LS; Weeks, S (Social Sciences Research Network, 2021)
Background: There is an urgent need to develop a simplified risk tool that enables rapid triaging of SARS CoV-2 positive patients during hospital admission, which complements current practice. Many predictive tools developed to date are complex, rely on multiple blood results and past medical history, do not include chest X ray results and rely on Artificial Intelligence rather than simplified algorithms. Our aim was to develop a simplified risk-tool based on five parameters and CXR image data that predicts the 60-day survival of adult SARS CoV-2 positive patients at hospital admission.